The Arts and nature : biology and symbolism in Barcelona circa 1900 - Pere Capellà Simó (Col·lecció Singularitats, 2015)
In the period of Modernisme nature came to the fore as a boundless source of artistic inspiration. Influenced by the cult of nature, creators produced a poetic, symbolic, dreamlike set of images and ideas; at the same time, scientists, experiencing the repercussions of Darwinism, were initiating the debate between creationists and evolutionists. Anti-materialistic and idealistic thinking, which in some cases had coincided with the postulates of the theories of evolution, shaped the framework of sensibilities of the Symbolist movement, in which the landscapes of the soul ranged from approaching the unconscious to voyaging to unexplored islands. This book, an in-depth study of the interrelationship between the arts and nature, embraces all of these phenomena from a plural, organic point of view.